The Influence of Transformational Leadership , Work Environment and Digital Technology on Plant Department Employee Performance PT. Kalimantan Prima Persada - Ervica Zamilah (Islamic University of Kalimantan MAB Banjarmasin, 2024)
This research aims to investigate the impact of transformational leadership, work environment, and digital technology on employee performance in the Plant Department of PT Kalimantan Prima Persada, a mining company. In the challenging mining industry, transformational leadership is considered an approach that can enhance employee motivation and development. A supportive work environment, particularly concerning safety and employee development, has a positive impact on well-being and productivity. Additionally, the integration of digital technology, including automation, data analysis, and artificial intelligence, is identified as a key factor in improving operational efficiency and employee performance. Primary data obtained through questionnaires were used for analysis, employing multiple linear regression along with the F-test and t-test.The research findings indicate that transformational leadership, a supportive work environment, and digital technology significantly contribute to employee performance. Transformational leadership, emphasizing motivation and development, can create a safety-oriented and innovative work culture. A supportive work environment, especially in terms of safety and employee development, also proves to have a positive impact on well-being and productivity. The integration of digital technology, such as automation and data analysis, can enhance operational efficiency and employee performance.